A selective review on the issue of testing for a unit autoregressive root - Αγιακλόγλου, Χρήστος Ν. (SPOUDAI Journal of Economics and Business, 1999)
In the recent few years an increasing effort has been made to establish reliable testing procedures to determine whether or not an observed time series is generated by a unit autoregressive root process. This paper presents in a selective manner some of the most common and widely used test statistics for testing for a unit autoregressive root and evaluates the performance of these test statistics in moderately large samples.